2022
DOI: 10.3389/fphys.2022.949044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of primary lesions in cytoskeleton proteins on red cell membrane stability in patients with hereditary spherocytosis

Abstract: We investigated by targeted next generation sequencing the genetic bases of hereditary spherocytosis in 25 patients and compared the molecular results with the biochemical lesion of RBC membrane obtained by SDS-PAGE analysis. The HS diagnosis was based on available guidelines for diagnosis of congenital hemolytic anemia, and patients were selected because of atypical clinical presentation or intra-family variability, or because presented discrepancies between laboratory investigation and biochemical findings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…com/article/10.3390/ijms242317021/s1. References [8,35,[60][61][62][63][64][65][66][67][68] Funding: This research received no external funding.…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
“…com/article/10.3390/ijms242317021/s1. References [8,35,[60][61][62][63][64][65][66][67][68] Funding: This research received no external funding.…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
“…(phosphofructokinase, aldolase, and glyceraldehyde-3phosphate dehydrogenase) (Lux, 2016;Pretini et al, 2019) ensures the average elasticity of erythrocyte membranes and the deformability of red blood cells. Previous studies have shown that abnormal proteins on the erythrocyte membrane can lead to the appearance of spherical cells, changes in cell osmotic pressure, and impairments in the ability of cells to perform normal circulation functions (Vercellati et al, 2022). Abnormal membrane proteins not only affect the physiological and biochemical properties of cells but also lead to blockage of blood circulation.…”
Section: Introductionmentioning
confidence: 99%